Symmetrical double‐comb multi‐slotted large bandwidth antenna for intelligent transportation systems. Issue 1 (9th October 2018) - Tripathi, Shivesh; Pathak, Nagendra P.; Parida, Manoranjan
Abstract: This article presents a novel compact circularly polarized multi‐slotted large bandwidth antenna for intelligent transportation system (ITS). The proposed antenna has a rectangular shaped multi‐slotted patch on upper side and a partial ground plane with multiple slots on lower side. The designed prototype antenna works from 22 to 29 GHz and is therefore applicable for ITS and weather forecasting applications. The design structure is distinct in terms of a low profile as well as simple structure, which is advantageous in mass production. Moreover, the multiple slots design antenna provides enhanced bandwidth. The axial ratio shows that the proposed antenna's behavior is circularly polarized with a compact size of 30 × 20 mm 2 . The measured reflection coefficient, gain, and the radiation pattern are consistent with simulated results. The proposed antenna has a reflection coefficient below −20 dB and maximum gain of ~5 dBi at 24 GHz (ITS band).